Seguimiento multidisciplinario en el control del penfigoide de membranas mucosas - Jeremias, Fabiano [UNESP]; Andrade, Cleverton Roberto de [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP] (My University, 2011)
The term Mucous Membrane Pemphigoid includes a group of chronic and autoimmune vesiculobullous diseases involving mainly the mucosa. The aim of present paper is to describe two clinical cases of Mucous Membrane Pemphigoid with gingival involvement to arrive to a proper diagnosis of the lesion and also to discuss the therapeutic behavior. Different complementary examinations were conducted including Nikolsky test, incisional biopsy, the LE cells study and of antinuclear antibodies, as well as the evaluation of dermatologists and ophthalmologists. It was necessary the replacement of toothpastes, the nutritional and psychological guiding, the hygiene care and the use of topic corticoids. There were periods of remission and exacerbation of clinical picture during follow-up being necessary the therapeutics fitting and the oral hygiene care reinforcement. It is important the multidisciplinary interaction in the care of these cases for treatment and follow-up control, as well as to reinforce all orientations and cares related to oral hygiene and the caution in the use of corticoids.
Multidisciplinary follow-up in mucous membranes pemphigoid control
Keywords: Desquamative gingivitis; Oral mucosa; Pemphigoid